Preliminary Design and Development of Open Field Antenna Test Site - Wibowo, Ignatius Agung; Mohamed Jenu, Mohammad Zarar; Alireza, C. (International Journal of Integrated Engineering, 2010)
An open area test site (OATS) for electromagnetic compatibility (EMC) antennas calibration will be built at the campus of Universiti Tun Hussein Onn Malaysia (UTHM) in Batu Pahat, Johor, Malaysia. The calibration of the EMC antenna mainly is to determine the antenna factor (AF). The development of the test site will be through modeling, simulation, selection of test site location, test site construction, and evaluation phases. The location of the test site will be selected so that it will have low ambient noise. The test site will be constructed based on the specification obtained from the model and simulation. Site attenuation measurements will be performed to evaluate the quality of the test site. This paper discusses a preliminary design and development of the test site includes feasibility study, design of the site construction, and measurements on site attenuation for site validation.